BIOLOGY OF NOTOPTERUS NOTOPTERUS (PALLAS) RAISED IN SMALL PONDS OF ASSAM - BORAH, BIBHA CHETIA; GOGOI, RIMZHIM; RAHMAN, ABDUR; HUSSAIN, MUSTAHID (Journal of the Inland Fisheries Society of India, 2021)
The present communication includes certain biological aspects of Notopterus notopterus (Pallas) raised in ponds (100 m2) of Assam. The length-weight relationship showed linear relationship for male (Log W= -1.935+ 2.841 Log L), female (Log W= -2.514+ 3.269 Log L) and sexes combined (Log W= -2.437+ 3.211 Log L). The analysis of the gut contents showed presence of bivalves, crustaceans, insects, etc. The average relative length of gut recorded in the present study was 0.54, which reveals that the species is basically carnivorous in nature. The fecundity of the species ranged from 340- 4493 nos. in fishes of weight ranging from 30- 290 g and total length of 16.7- 32.5 cm. In females of N.notopterus, the G.S.I ranged from 0.63- 8.25, while in males it ranged from 0.15-1.08, with highest value in June. The pattern of gonadal development indicated that the species breeds once in a year with breeding period commencing from April to July, with peak during May-June. The study revealed that the species grows well and breeds naturally in pond condition and can be a potential candidate for utilization of small homestead ponds available in almost every household of rural Assam, which are not suitable for culture of carps for securing protein nutrition to rural resourcepoor household.Key words: Notopterus notopterus, length-weight relationship, gonado somatic index, fecundity, ova-diameter, carnivorous